A history of modern Uganda - Reid, Richard J. (Richard James) (Cambridge, United Kingdom : Cambridge University Press, 2017)
This book is the first major study in several decades to consider Uganda as a nation, from its precolonial roots to the present day. Here, Richard J. Reid examines the political, economic, and social history of Uganda, providing a unique and wide-ranging examination of its turbulent and dynamic past for all those studying Uganda's place in African history and African politics. Reid identifies and examines key points of rupture and transition in Uganda's history, emphasising dramatic political and social change in the precolonial era, especially during the nineteenth century, and he also examines the continuing repercussions of these developments in the colonial and postcolonial periods. By considering the ways in which historical culture and consciousness has been ever present - in political discourse, art and literature, and social relationships - Reid defines the true extent of Uganda's viable national history. --
Explanations, apologies and acknowledgements -- List of maps -- Prologue: a view from the museum -- 1. Refractions: beholding Uganda -- 2. Pensive nation: the age of blood and rebirth -- 3. Rukidi's children: the trials and tribulations of Kabalega and Mwanga -- 4. The adventures of Zigeye and Atuk: the age of opportunity and disparity -- 5. Kings and others: history and modernity -- Epilogue: managing time and space -- Sources and bibliography -- Index.
Includes bibliographical references (pages 357-394) and index.
Keywords: 2000-2099; Civilization; Colonial influence; Manners and customs; Politics and government; Social conditions; Uganda -- History; Uganda -- 21st century -- History; Uganda -- Politics and government; Uganda -- Colonial influence; Uganda -- Civilization -- 21st century -- History; Uganda -- Social life and customs -- History; Uganda -- Social conditions -- History; Uganda; History